(untitled) - Letterman, Raymond D. (New York, 1999)
The leading source of information on water quality, water treatment, and quality control for 60 years is now available in an up-to-the-minute new edition. The American Water Works Association's Water Quality & Treatment, Fifth Edition fully covers the field, bringing you the expertise of 20 distinguished specialists who provide the latest information on everything from aeration and coagulation processes, to chemical oxidation and water plant waste management. At least 90% of the material in this new edition has been revised and updated.
Keywords: Water supply engineering,Water treatment,Water; Purification,Filtration